MEWUJUDKAN DESA TANPA KEMISKINAN DAN KELAPARAN DI JAWA TENGAH DENGAN DANA DESA (2019-2020) - Suparjito Bin Karnoto; Artika Taryani; Nadia Nur Rahma; Nur Sukma Alam; Rizma Yunita Eka Putri; Rr. Raina Avissa Dione Belindasari (JURNAL PEMBANGUNAN EKONOMI DAN KEUANGAN DAERAH, 2022)
This study focuses on the role of using village funds to realize the Sustainable Development Goals (SDGs) program. The Village SDGs focus on at least three things, namely, poverty, food sustainability, and stunting. With the release of Perpres 59/2017 tentang Pelaksanaan Pencapaian Tujuan Pembangunan Berkelanjutan, the purpose of distributing village fund has become clearer. The Analytical method used in this paper is statistical analysis using Pearson correlation to measure the correlation between the amount of village fund and the poverty index, the food sustainability index, and the number of stunting. Pearson correlation shows that the correlation between village funds and poverty has a fairly strong positive relationship in 2019 and a weak positive relationship in 2020. The same is also shown by the correlation between village fund and stunting which results in a weak positive relationship in both years. on the other hand, Pearson correlation shows that the correlation between village fund and the food sustainability index has a fairly strong negative relationship during 2019 and 2020.